The Causal Effect of Parents' Schooling on Children's Schooling: A Comparison of Estimation Methods - Holmlund, Helena; Lindahl, Mikael; Plug, Erik (Journal of Economic Literature, 2011)
We review the empirical literature that estimates the causal effect of parent's schooling on child's schooling, and conclude that estimates differ across studies. We then consider three explanations for why this is: (a) idiosyncratic differences in data sets, (b) differences in remaining biases between different identification strategies, and (c) differences across identification strategies in their ability to make out-of-sample predictions. We conclude that discrepancies in past studies can be explained by violations of identifying assumptions. Our reading of past evidence, together with an application to Swedish register data, suggests that intergenerational schooling associations are largely driven by selection. Parental schooling constitutes a large part of the parental nurture effect, but as a whole does not play a large role. (JEL I21, J13)